Adherence to Anti-Retroviral Therapy among People Living with HIV and AIDS in Far West, Nepal - Bam, Kiran; Karki, Deepak Kumar; Lohani, Shyam Prasad; Thapa, Rajshree; Aryal, Umesh Raj; Pathak, Laxmi Raj (Asian Journal of Medical Sciences, 2011)
Objective: Adherence to Anti-Retroviral Therapy is a principal predictor for the success of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) treatment. It remains as a challenge to AIDS treatment and care with the wide spread of the associated risks. The study aims to assess adherence level and factors associated with adherence to Anti-Retroviral Therapy (ART) among people living with HIV and AIDS in Far West, Nepal. Material & Methods: A cross sectional study was carried out in Far West between May 2009 to September 2009. A total of 176 samples allowed with 95% CI and 5% error proportionately from four ART sites were drawn. Random sampling technique was used to recruit patients. Semi-structured questionnaire schedule adapted from the Adult AIDS Clinical Trials Group (AACTG) was used and pre-tested to collect data on drug adherence. We compared non-adherent patients with adherent patients and associations with key risk factors were determined. Results: An overall self reported adherence for a month was 84%. Those who were more than 95% adherent responded that use of watch, electronic devices such as mobiles, watch and calendar facilitated them to take the drugs regularly. Improved adherence was significantly determined by time to reach the health faility at terai (OR: 2.86, 1.10-7.47), disclosing of the HIV status (OR: 3.25; 1.02-10.19), the perceived positive benefits of ART (OR: 21.07; 6.79-68.04) and excellent satisfaction with the provider (OR: 13.11; 4.75-36.19). Travel cost more than 2$ (OR: 9.84; 3.44-28.73) was significant barrier to adherence. Conclusion: Timely detection of non-adherence behaviours and understanding of patients' difficulties with ART could potentially help patients for adherence and therefore improve the treatment outcomes in rural hilly Nepal. Government’s initiatives towards moral support for encouraging to join support group including discussions of side-effects, and everyday problems in sticking to a regimen and financial support to PHLA should be promoted to optimize the adherence rate. Key Words: Adherence; ART; PLHA; Far West Nepal DOI: 10.3126/ajms.v2i1.4290 Asian Journal of Medical Sciences 2 (2011) 7-13